A DEMATEL-based analysis of logistics determinants in online retail - Nicollas Luiz Schweitzer de Souza Schweitzer; Marina Bouzon; Diego de Castro Fettermann; Enzo Morosini Frazzon (Brazilian Journal of Operations & Production Management, 2025)
Goal: The objective of this study is to perform the analysis of the logistical determinants for the purchase of a product online through the DEMATEL methodology. Design/methodology/approach: The factors that drive a customer to make a purchase online have become competitive and make it so that the customer can quickly compare online sales platforms and then select the one that is most attractive to them. This study sought through the DEMATEL methodology to identify with experts in the area, factors that lead a customer to make a purchase decision in an online retail in the logistics context. Results: The results show that the experience that the retailer delivers to the customer in the delivery logistics process is totally directed with the purchase decision and that this is a focus factor of the specialists in the decision-making process. Research limitations: Some data on logistics factors, customer preferences, or purchasing behavior may compromise the accuracy and reliability of the analysis results. Practical implications: Understanding the factors, businesses can optimize their supply chain processes to meet customer demands efficiently, reducing lead times, stockouts, and delivery delays. This may involve renegotiating contracts with shipping providers, investing in warehouse automation technology, or optimizing transportation routes to reduce costs and improve overall operational efficiency. Originality/value: Few studies have applied DEMATEL to logistics issues, especially in the context of online retail. This article seeks to point out indicators for decision-making that are rarely studied in the literature and that serve as a new way of helping managers make decisions.